Dampak Rasio Kesehatan Bank pada Kinerja Keuangan Bank Umum Syariah - Cicih Rusmini; Isro’iyatul Mubarokah (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2022)
This study aims to examine whether there is an impact between bank health ratios and financial performance. In determining the sample using the Purposive Sampling Method so as to obtain 6 samples. Research data obtained from the annual reports of each bank. The technique used in this research is multiple linear regression analysis. The results of the research by t test, financial performance is not influenced by the Capital Adequacy Ratio (CAR), but is influenced by Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Costs and Operating Income (BOPO). The results of the study using the f test, the bank's health ratio affects the financial performance of Islamic commercial banks.